Species Delimitation and Cryptic Diversity in Rheotanytarsus Thienemann & Bause, 1913 (Diptera: Chironomidae) Based on DNA Barcoding - Yuan Yao; Jia-Yu Chen; Xiao-Ling Gong; Chen-Hong Li; Zheng Liu; Xiao-Long Lin (Insects)
The genus Rheotanytarsus Thienemann & Bause, 1913 (Diptera: Chironomidae) currently includes more than 120 recognized species worldwide, but precise species-level identification based solely on morphology remains challenging. Pronounced morphological differences among life stages and the time-consuming inefficiency of rearing larvae further complicate life-stage matching in this genus. In this study, we assessed species diversity by integrating morphological examination and DNA barcoding, analyzing 911 DNA barcodes from newly collected samples and a public database. Based on these results, we further constructed a relatively complete life-history framework. Our results show that 911 Rheotanytarsus DNA barcodes belong to 69 putative species. The maximum intraspecific divergence reached 7.35% in R. pentapoda, and the average minimal interspecific distance was 11.44%. Substantial intraspecific divergence in certain species complexes suggests the presence of cryptic species. Therefore, to resolve these potential cryptic species issues, more extensive sampling and morphological examination of specimens from geographically distant regions—supplemented by nuclear and ecological data—are required.